IMPROVING INTERVENTION INTEGRITY OF DIRECT‐SERVICE PRACTITIONERS THROUGH PERFORMANCE FEEDBACK AND PROBLEM SOLVING CONSULTATION. (26th February 2014) - Minor, Lisa; DuBard, Melanie; Luiselli, James K.
<x xml:space="preserve">Abstract</x> The purpose of this study was to improve intervention integrity of behavior support plan implementation by teachers at a specialized school. During the first phase of a multiple baseline design, performance feedback was given to the teachers during (correction) and immediately following (praise) classroom observations. In a second phase, the teachers received problem solving consultation that addressed behavior support plan misapplication and respective procedural modifications. Only one of the three teachers demonstrated improved intervention integrity with performance feedback, whereas problem solving consultation produced uniform improvement. We discuss these findings and implications for intervention integrity assessment and research. Copyright © 2014 John Wiley & Sons, Ltd.